A Numerical Investigation of Thermal-Induced Explosive Spalling Behavior of a Concrete Material Using Cohesive Interface Model - Zhang, Jiuchang; Chen, Jiamin; Zhang, Rongwei; Guo, Rongxin (Frontiers in Physics, 2022)
Thermal-induced spalling is a typical failure behavior of concrete materials exposed to high temperatures. This study uses Abaqus to establish a numerical model of concrete material comprising aggregates and mortar matrix. Cohesive elements considering heat conduction are embedded into this numerical model to simulate the thermal-induced explosive spalling failure process of the concrete material. Simulation results show that the heat gradually transfers from the outer boundaries to the inner areas with increasing temperature. Thermal stresses concentrate in the aggregates-mortar interfaces, where thermal-induced cracks initiate and propagate. The occurrence of thermal-induced cracks reduces the heat conductivity of mortar, reduces thermal stresses and leads to severe spalling failure in the concrete material. This research provides a practical scheme for the numerical simulation of the thermal-induced spalling behavior of concrete materials.